Human rights of drug users according to public health professionals in Brazil - Ventura, Carla AA (Nursing ethics, 2013)
Health is a basic human right, and drug use represents a severe influence on people’s health. This qualitative study aimed to understand how health professionals in a public health-care team working with drug users in a city of the state of São Paulo, Brazil, perceive the human rights of these users and how these rights are being respected in health care. Data were collected through semistructured interviews with 10 health professionals at the service under analysis. A thematic analysis of the interviews reveals the professionals’ difficulty to define the concept of human right and contextualize these rights in their work environment. A deeper understanding of the right to health, however, represents an important premise for a more humanized care practice in health services to drug users.